The Child Labor In Indonesia: Working or Not, Working For A Wage or Not, and Child Labor Wages Function - Isra Yeni (Universitas Negeri Padang, 2018)
This study was conducted to investigate the phenomena of child labor in Indonesia using data from National Socio-Economic Survey (SUSENAS) 2014. First, investigate the impact of household economic condition and supervision of mothers on probability of child’s work or not. Furthermore, this study looked at the effects of parents occupation on the probability of child working receive a wage or not. Finally, this study estimates of child labor wage function. The method used is sequential Probit models, where each decision made in sequence according to a binary Probit model, and also used is Ordinary Least Square model. On the first Probit model, a significant association between household economy conditions on the probability of child labor participation is found. Second Probit model, the results shows that parent occupation of agriculture sector will encourage children to work did not receive a wages. The estimated OLS models shows that, the level of education is an investment that is most important for children to increase their income, especially in the future.